Philosophy for Communites al Liceo “Govone” di Mondovì (Italy) - Bevilacqua, Silvia; Casarin, Pierpaolo (ETHICS IN PROGRESS, 2017)
In this contribution we shall focus on the project of philosophy for communities carried out at the Liceo “Vasco-Beccaria-Govone” (Mondovì , Italy) within the IX edition (2016) of the CeSPeC Summer School on Futures, imagining the world of tomorrow. Philosophy is understood as a practice, an experience, a creation of concepts, an inquiry, as an exercise of argumentation and research. Thanks to this view, a dialogue has opened up with the pupis of this school. In this contribution we present the perspective of a post-philosophy for children and we understand it as an opportunity for philosophy in itself.